THE INFLUENCE OF PEER SUPPORT ON THE ENTREPRENEURIAL MINDSET OF STIBA AR RAAYAH STUDENTS - Khatimah, Husnul; Nuradi; Huryatul Muhafizhah; Najmah (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2025)
An entrepreneurial mindset is an essential element in shaping the entrepreneurial character of students, especially in the context of higher education based on Islamic values. This mindset encourages students to dare to take risks, think innovatively, and make business activities a means of self-actualisation and worship. This study aims to analyse the influence of peer support on the entrepreneurial mindset of female students of the Islamic Communication and Broadcasting Study Program, STIBA Ar Raayah, Sukabumi. Islamic entrepreneurship is an economic activity and a manifestation of worship based on ethics, justice, and spirituality. This study uses a quantitative approach with a survey method, and data analysis is carried out using Structural Equation Modelling (SEM) techniques based on Partial Least Squares (PLS). A total of 23 active female students in the fifth semester were made respondents. The analysis showed that peer support positively and significantly influenced entrepreneurial mindset, with a path coefficient of 0.792. These findings confirm the importance of a supportive social environment in shaping student entrepreneurial mindsets. This study recommends strengthening entrepreneurship programmes based on Islamic values through a collabourative approach between students in a higher education environment to create an ecosystem that supports the growth of Muslim entrepreneurs with competitiveness and integrity.